Interventional cardiac catheterization in neonatal age: results in a multicentre Italian experience. (1st September 2020) - Giordano, Mario; Santoro, Giuseppe; Agnoletti, Gabriella; Carminati, Mario; Donti, Andrea; Guccione, Paolo; Marasini, Maurizio; Milanesi, Ornella; Russo, Maria Giovanna; Castaldi, Biagio; Cheli, Martino; Formigari, Roberto; et al.
Abstract: Background: Despite recent technical advances, interventional cardiac catheterization is still challenging in neonatal age and no specific data concerning early outcome are so far published in literature. Methods: Neonatal trans-catheter cardiac interventions performed in high-volume Italian referral centers were retrospectively analyzed. Primary outcomes were procedural major adverse events, in-hospital mortality and procedural failure. Secondary outcomes were minor adverse events and need for blood transfusion. Results: From January 2000 to December 2017, 1423 newborns (mean weight 3.0 ± 0.6 kg, range 1.0–5.8; median age 2.0 days) underwent interventional cardiac catheterization. Overall, global procedure adverse event rate and in-hospital mortality were 10.2% and 5.2%, respectively. At multi-variable analysis, primary composite outcome was significantly related to low-weight (<2.5 kg) (p < 0.01) and younger age (≤7 days) (p < 0.01) at the procedure, prematurity (p < 0.01), uni-ventricular physiology (p < 0.01), associated genetic syndromes (p < 0.01) and procedure risk category (p < 0.01). No relationship between volume of activity of any single center and procedure outcome was found. Over time, a trend toward an increased number of procedures and their complexity was recorded. Trans-catheter management of cardiac malformations with critical, duct-dependent pulmonary blood flow by arterial duct stenting or right ventricular outflow tract stenting showed the highest increase. Conclusions: Interventional cardiac catheterization is relatively safe and feasible in neonatal age. Peri-natal age, low weight, uni-ventricular physiology and genetic syndromes still significantly contribute to procedural morbidity and in-hospital mortality of this approach. Highlights: Interventional catheterization in newborns is an effective and safe approach. Major adverse events rate is influenced by the complexity of the procedure. Mortality depends on the clinical and hemodynamic characteristics of newborn. Over time, an increase in number and complexity of procedures was recorded.